EFEKTIVITAS BAHASA VISUAL POSTER UNTUK MENGETAHUI DAMPAK NEGATIF NARKOBA BAGI MAHASISWA PADA KAMPANYE ANTI NARKOBA DI LINGKUNGAN KAMPUS MERCU BUANA DENGAN MODEL EPIC - Ulita, Novena; Fahlan, Ahmad Syauqi; Hakam, Abdurrahman; Argakusmah, Lucky; Islami, Intan (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2024)
Posters are one of the media that is close to reaching students to convey information or messages. As an educational institution, Mercubuana University actively provides education for students, one of which is voicing the dangers of drugs for students. The Anti-Drug Campaign carried out by Mercubuana University uses posters posted around the campus. However, as a campaign it is necessary to evaluate the level of effectiveness of the media in conveying information/messages to students so that it achieves the intended goals. To know this, several theories are needed, including visual language theory, color theory, and the EPIC model of communication effectiveness theory. The method used in this research is a quantitative method with a Likert scale using the EPIC model approach. The EPIC variable (empathy, persuasion, impact, communication) is used to measure the effectiveness of posters as part of campaign media. The results of this research show that there is the influence of visual elements, especially illustration elements, which can build persuasion with a value of 4.33, so that visual elements greatly influence the effectiveness of a poster, especially illustration attributes. Thus, in this research, it is proven that posters are an effective medium in conveying messages in the anti-drug campaign carried out by Mercubuana University. In particular, posters are effective because they are influenced by illustration, color and typography attributes that build the visual language of the campaign and this needs to be taken into account by designers.Keywords: effectiveness, social campaign, poster, visual language, visual communication, EPIC Model